The Strategy of Translation of Foshan Paper-cut Culture from the Perspective of Communication - Li Zhou (Journal of Linguistics and Communication Studies, 2024)
The translation of Foshan paper-cut holds significant importance in cross-cultural communication and exchanges. This paper, from the perspective of communication, in combination with the actual examples of Foshan paper-cut culture translation, proposes the fundamental principles of Foshan paper-cut culture translation, explores the translation strategies and methods of Foshan paper-cut culture translation, with the aim of contributing to the cross-cultural communication of Foshan paper-cut culture, which is of considerable significance for promoting Foshan culture.